2011
DOI: 10.5194/bg-8-2437-2011
|View full text |Cite
|
Sign up to set email alerts
|

Diel variations in the carbon isotope composition of respired CO<sub>2</sub> and associated carbon sources: a review of dynamics and mechanisms

Abstract: Abstract. Recent advances have improved our methodological approaches and theoretical understanding of postphotosynthetic carbon isotope fractionation processes. Nevertheless we still lack a clear picture of the origin of shortterm variability in δ 13 C of respired CO 2 (δ 13 C res ) and organic carbon fractions on a diel basis. Closing this knowledge gap is essential for the application of stable isotope approaches for partitioning ecosystem respiration, tracing carbon flow through plants and ecosystems and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 156 publications
4
27
1
Order By: Relevance
“…Similar trends regarding 13 C distribution were previously reported by other authors (Ghashghaie et al 2003;Badeck et al 2005;Gessler et al 2009;Wegener, Beyschlag, and Werner 2010;Hunching 2011;Werner and Gessler 2011;Ghashghaie and Badeck 2014).…”
Section: Stable Isotope Measurementssupporting
confidence: 90%
“…Similar trends regarding 13 C distribution were previously reported by other authors (Ghashghaie et al 2003;Badeck et al 2005;Gessler et al 2009;Wegener, Beyschlag, and Werner 2010;Hunching 2011;Werner and Gessler 2011;Ghashghaie and Badeck 2014).…”
Section: Stable Isotope Measurementssupporting
confidence: 90%
“…7). The potential biological mechanisms that would lead to diel variation in δ 13 C of respiration have been recently reviewed (Werner and Gessler, 2011) and include variation in respiratory substrate, isotopic fractionation, and/or changes in relative amounts of component fluxes such as autotrophic (rhizospheric) and heterotrophic respiration. There is compelling evidence for a short-term linkage between photosynthesis and belowground respiration (Kuzyakov and Gavrichkova, 2010), almost certainly mediated by the roots and their symbionts (Hopkins et al, 2013;Savage et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Others have used δ 13 C of soil efflux to assess the relative contributions of autotrophic and heterotrophic respiration (Kuzyakov, 2006) or added isotopic labels via organic material (Bird and Torn, 2006) or via photosynthesis (Högberg et al, 2008) to investigate soil carbon cycle processes. Several studies have identified diel variation in the δ 13 C of plant and soil respiration (reviewed by Werner and Gessler, 2011), and others have highlighted changes in rate and δ 13 C of soil efflux following rain (e.g., Jarvis et al, 2007;Unger et al, 2012). Presumably such changes involve the varied consumption of organic substrates for heterotrophic activity that differ systematically in δ 13 C, such as starch, lignin, or cellulose .…”
Section: R Bowling Et Al: Environmental Forcing Does Not Induce mentioning
confidence: 99%
“…This method has often been used to understand the impact of environmental variables on the C cycle (see reviews by Brüggemann et al, 2011;Kuzyakov & Gavrichkova, 2010;Mencuccini & Hölttä, 2010), even though recent studies have highlighted the need to deal with confounding effects, which might modify the isotope signal between assimilation and respiration. Such effects include diel variations of δ 13 C in respired CO 2 , postphotosynthetic and respiration fractionation and damping of the 13 C signal as it is transferred below ground (Gessler, Tcherkez, Peuke, Ghashghaie, & Farquhar, 2008;Kodama et al, 2008;Werner & Gessler, 2011). Furthermore, in recent years, biological controls (ontogeny, physiological adaptation to biotic and abiotic environment) have emerged as additional important drivers of short-term C dynamics and its isotope signature (e.g., Bathellier et al, 2008;Ghashghaie & Badeck, 2014;Ghashghaie et al, 2015;Salmon, Barnard, & Buchmann, 2011Salmon, Buchmann, & Barnard, 2016).…”
Section: Introductionmentioning
confidence: 99%